Neuropathogenesis in COVID-19 - Altable, Marcos; De la Serna Tuya, Juan Moisés (Journal of Neuropathology & Experimental Neurology, 2021)
SARS-CoV-2 or COVID-19 is a new human coronavirus that emerged in Wuhan, China in late 2019 and is currently causing a pandemic (1, 2). With the possibility of future outbreaks of the disease, it may manifest with diverse clinical characteristics and different severity, as has been seen with other viruses. COVID-19 belongs to a large family of RNA viruses that have been considered a global health problem because they have a remarkably high transmissibility potential and sometimes invade the CNS (3–5). Because of the rapid expansion of a virus that until now was unknown, it is important to understand the mechanisms by which COVID-19 generates CNS disease. Understanding CNS involvement in the disease is especially challenging and current theories of pathogenesis include direct neuroinvasion, crossing of the blood–brain barrier (BBB) by the virus, and a nicotinic hypothesis.
Keywords: COVID-19; JCR; Scopus